N-Bromosaccharin as an Analytical Reagent for Micro Determination of Acridine Derivatives in Acetic Acid - Chauhan, R.P.S.; Kumar, Manoj (Asian Journal of Chemistry, 2010)
In the present work, the method for the small-scale determination of acridine derivatives with the use of N-bromosaccharin as an analytical reagent has been described. This gives reproducible results within the accuracy of ±1%.